ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA MANAJERIAL PADA INDUSTRI MANUFAKTUR DI JAWA TENGAH - Hariyanti, Widi (Fakultas Ekonomi - Universitas Setia Budi, 2018)
This study examined the effect budget adequacy, timelines accountancy management information and organizational commitment on managerial performance, by using the unit analysis is manager who worked at the manufacturing company in Central Java. The sampling technique used is the purposive method, where the entire population sampled. Result from data processing, so can be taken conclusion as follows there positive influence and significant between variable budget adequacy, timelines accountancy management information and organizational commitment on managerial performance. The feasibility test results of the research model show a positive value significant influence between variables budget adequacy, timelines accountancy management information and organizational commitment are simultaneously on variable managerial performance. Result analysis of the coefficient determination indicates that the variables budget adequacy, timelines accountancy management information and organizational commitment variation affecting the variable managerial performance.